PENANAMAN NILAI-NILAI KARAKTER DALAM PENDIDIKAN AGAMA ISLAM MELALUI METODE BERCERITA DI SD N 07 SUMANIK KECAMATAN SALIMPAUNG KABUPATEN TANAH DATAR - Mhd. Aulia Firman Puldri (IAIN Batusangkar, 2017)
The problem in this research is the cultivation of character values by PAI teacher through storytelling and character values any implanted through storytelling. The purpose of this study is to describe the process of cultivation of character values in Islamic education through storytelling. The method used a qualitative research method with type research field research is descriptive qualitative. The data source is the PAI teacher. The research location is in SD N 07 Sumanik Salimpaung District of Tanah Datar. Namely data collection techniques of observation, interviews and documentation. Data processing techniques by collecting data, once collected then checked and diklasifiasikan, so make easy in data processing. Analysis of the data used is, selecting the data, classifying the data, content analysis, and conclusion. Technique authenticity of data is triangulation is using a variety of sources, such as interviews with respondents and researcher observation and documentation. The results showed that the learning process in primary PAI SD N 07 Sumanik Salimpaung District of Tanah Datar, through storytelling in the cultivation of character values categorized as good, with storytelling techniques without the help of using media images. However, there are some components of storytelling process that has not been done as it should be, as in the stage of arranging the seating of students, at this stage of asking the students to retell the stories that have been submitted. From the stories presented by the teacher in the classroom learning process PAI their character values are imparted to students, among others: (1) The value of character religious, (2) honest, (3) tolerance, (4) hard work, ( 5) curiosity, (6) the national spirit, (7) recognize excellence, (8) friends / communicative, (9) love peace, (10) social care, and (11) of responsibility. While the character values (1) discipline, (2) independent, (3) democratic, (4) likes to read, (5) love of the homeland, (6) creative, and (7) to care for the environment has not seen imparted to students through methods of the story told.